Passiflora nosferatu sp. nov., the second exclusively unipetalous species within Passiflora supersect. Tacsonia (Passifloraceae); including notes on P. brachyantha from central-southern Ecuador - Kuethe, J.r.; Wettges, Martin; Garzón-Suárez, Henry X.; Magdalena, Carlos; Torres, Andrés; Jiménez, Marco M.; Cornejo, Xavier (Phytotaxa, 2025)
Two rare endemic species of genus Passiflora (Passifloraceae) from Ecuador have been studied and illustrated. This study has uncovered a new consistently unipetalous species closely related to the Ecuadorean P. unipetala. Field studies have shown maintainable vegetative and floral differences between the new species from Bolívar province proposed here as Passiflora nosferatu sp.nov. and P. unipetala found just west of Quito in Pichincha province. A comparison between P. unipetala and P. nosferatu has been provided, along with notes on the conservation, distribution, ecology and taxonomy of these two species. In addition, this study provides new and improved notes on P. brachyantha, a species of P. supersect. Tacsonia found only in southern Ecuador. This species is showing an alarming decline in population and distribution, where much of its original forest has been destroyed. Two new populations were observed, though recent road construction has already damaged both these localities leaving the future of the species uncertain.